The interaction between the gene SOD1 rs2070424 and the plasma zinc/copper ratio predicts renal function impairment - Chen, Jingsi; Ge, Jiaju; Song, Jiayuan; Wang, Tianci; Ma, Yuqin; Qian, Xiaoyan; Zhou, Chang; Wang, Qiuguo; Zhu, Senlin; Wu, Xiyu; Du, Hongzhen; Qin, Liqiang; et al. (Frontiers in Nutrition, 2025)
BackgroundEssential trace elements zinc and copper have been suggested to play a role in renal function. However, the balance between these elements and their interaction with genetic variation in Superoxide Dismutase 1 (SOD1) remains unclear.MethodsWe conducted a prospective study involving 1,274 middle-aged and elderly participants from the “135” cohort in 2015. Cox regression analyses were used to assess associations between plasma trace elements, SOD1 polymorphism (rs2070424), and their interactions with impaired renal function. To assess predictive performance, we compared discrimination and reclassification using ROC analysis, as well as the net reclassification index (NRI) and integrated discrimination improvement (IDI).ResultsAfter adjusting for multiple variables, the hazard ratios (HRs) (95% CI) comparing the highest to the lowest tertiles were 1.303 (1.037, 1.637) for zinc, 1.615 (1.275, 2.046) for the zinc/copper ratio, and 0.709 (0.558, 0.900) for copper. Compared with the GG genotype, the AG and AA genotypes were positively associated impaired renal function (HR: 1.282, 95% CI: 1.003, 1.639). Positive associations between impaired renal function and plasma zinc (P for interaction: 0.006), as well as the zinc/copper ratio (P for interaction: <0.001), were modified by rs2070424 genotypes. The adjusted HRs comparing tertile 3 with tertile 1 for impaired renal function were: AA/AG carriers—zinc 1.359 (1.055–1.749); zinc/copper ratio 1.642 (1.267–2.128); GG carriers—zinc 1.065 (0.623–1.819); zinc/copper ratio 1.584 (0.889–2.822). In prediction analyses, the zinc/copper ratio showed higher discrimination (AUC) than single-metal models and improved reclassification (NRI, IDI), providing partial evidence of incremental value.ConclusionDecline in renal function was positively correlated with plasma zinc and the zinc/copper ratio and negatively correlated with plasma copper. The relationship between impaired renal function and both zinc and the zinc/copper ratio was modified by rs2070424 genotypes. Taken together, considering zinc/copper ratio provides a more informative summary than single-metal measures and shows partial incremental discrimination.